Puzzlingly low utilization of solar irrigation pumps by smallholders in Nepal undermines cost-effectiveness - Oziel, Dan; Mukherji, Aditi; Lamichhane, Nabina; Fishman, Ram (IOP Publishing, 2024)
Solar powered irrigation pumps (SIP) hold substantial potential for low carbon irrigation expansion, particularly where affordable electricity is limited. In contrast to diesel-based irrigation, which carries steep fuel costs, irrigation by SIP requires zero marginal costs, but high initial investments. This makes their competitiveness with diesel pumps highly dependent on the temporal frequency of their usage. Using unique and detailed data on SIP usage by smallholders in Nepal, we show SIP usage frequency is low, making it financially competitive with diesel for only a small fraction of farmers. We analyze characteristics of farmers who make low/high usage of the SIP, and explore potential explanations for the puzzling low level of SIP use.